Determinants of maintenance performance: A resource-based view and agency theory approach (2019)
This study aims to examine the effects of maintenance service firms’ resources and capabilities on maintenance performance, measured by the turnaround time of medical devices (TAT). The theoretical framework used in this study is based on the resource-based view (RBV) and agency theory (AT). The hypotheses were tested using information on 764 medical devices and 60 maintenance service providers, resulting in 1403 maintenance transactions. As such, our data sample is significantly larger than those used in previous studies in this area. For this study we used a variation of the proportional hazards model, the conditional frailty gap time hazards model. The empirical analysis of this research is among the first to quantify how the performance of maintenance providers is affected by the core constructs of both the resource-based view and agency theory, using statistical evidence. © 2019